A frequent splicing mutation and novel missense mutations color the updated mutational spectrum of classic galactosemia in Portugal. Issue 1 (8th June 2013) - Coelho, Ana I.; Ramos, Ruben; Gaspar, Ana; Costa, Cláudia; Oliveira, Anabela; Diogo, Luísa; Garcia, Paula; Paiva, Sandra; Martins, Esmeralda; Teles, Elisa Leão; Rodrigues, Esmeralda; Cardoso, M. Teresa; et al.
Abstract: Classic galactosemia is an autosomal recessive disorder caused by deficient galactose‐1‐phosphate uridylyltransferase (GALT) activity. Patients develop symptoms in the neonatal period, which can be ameliorated by dietary restriction of galactose. Many patients develop long‐term complications, with a broad range of clinical symptoms whose pathophysiology is poorly understood. The high allelic heterogeneity of GALT gene that characterizes this disorder is thought to play a determinant role in biochemical and clinical phenotypes. We aimed to characterize the mutational spectrum of GALT deficiency in Portugal and to assess potential genotype‐phenotype correlations. Direct sequencing of the GALT gene and in silico analyses were employed to evaluate the impact of uncharacterized mutations upon GALT functionality. Molecular characterization of 42 galactosemic Portuguese patients revealed a mutational spectrum comprising 14 nucleotide substitutions: ten missense, two nonsense and two putative splicing mutations. Sixteen different genotypic combinations were detected, half of the patients being p.Q188R homozygotes. Notably, the second most frequent variation is a splicing mutation. In silico predictions complemented by a close‐up on the mutations in the protein structure suggest that uncharacterized missense mutations have cumulative point effects on protein stability, oligomeric state, or substrate binding. One splicing mutation is predicted to cause an alternative splicing event. This study reinforces the difficulty in establishing a genotype‐phenotype correlation in classic galactosemia, a monogenic disease whose complex pathogenesis and clinical features emphasize the need to expand the knowledge on this "cloudy" disorder.